The Baltic banking system in the enlarged European Union: The effect of the financial crisis on efficiency - José L. Gallizo Larraz; Jordi Moreno; Manuel Salvador (Baltic Journal of Economics, 2018)
The main objective of this study is to analyse the evolution of banking efficiency in the Baltic countries after their accession to the EU and during the financial crisis, and to check whether there are significant differences between these countries as a consequence of their particular characteristics. To that end, we have estimated the evolution of cost and profit efficiency in the Baltic countries in the context of the enlarged EU during the period 2000-2013 using Bayesian stochastic frontier models. Our results show the greater robustness of Estonian banking in terms of profits during the financial crisis in comparison to their neighbours. Additionally, Baltic banking has recovered its profit efficiencies very quickly after the financial crisis. However, cost efficiency is still at low levels in line with the other European countries.
Keywords: G14; G21; 330; Banking efficiency; economic crisis; stochastic frontier models; Bayesian inference